Relationship between Human Activities and Deforestation in Karongi District of Rwanda - Nishimwe, Olive; Hakizimana, Narcisse; Nahayo, Lamek; Maniragaba, Abias; Nirere, Theodore (Journal of Forests, 2021)
Karongi District of Rwanda is one among districts with high rate of forest clearance resulting from unmanageable human activities and change on land use. This study was conducted in order to analyze the relationship between human activities and deforestation on the period between 2013 and 2019. The authors employed secondary data on forest cover collected from the Rwanda Forestry Authority (RFA), National Institute of Statistics of Rwanda (NISR), and Karongi District report. Thereafter, the Geographic Information System (GIS) helped to map forest cover and Microsoft Excel was used to indicate the percentage of land cover change over the study period. The Pearson correlation analysis of the Statistical Package for Social Sciences (SPSS) analyzed the relationship between human activities and deforestation in Karongi District. The results showed that between 2013 and 2019, cropland, built up and population growth rate increased at the rate of 5 %, 2.15%, and 6.07% respectively. The forestland which reduced by 5.4% in the same period generated a positive significant relationship between population growth and forestland with correlation r1= 0.993. The results also revealed a positive significant relationship between settlement and forestland with r2=0.990. The negative significance relationship between cropland expansion and forestland with r3 = -0.970 at 0.05 level of significance was noticed. Since the analysis generated a positive effect of settlements and population growth on deforestation, it can be concluded that human activities contribute to deforestation in Karongi District of Rwanda, and that relevant measures should be applied.